Desalination of brackish groundwater and reuse of wastewater by forward osmosis coupled with nanofiltration for draw solution recovery - Giagnorio, Mattia; Ricceri, Francesco; Tiraferri, Alberto (Water research (Oxford), 2019)
This study evaluates a treatment system centered on forward osmosis (FO) to extract high-quality water from real brackish groundwater and wastewater. The groundwater had salinity of 4 g/L, while the wastewater sample consisted of a secondary effluent. These feed solutions were treated first in a FO step, achieving a recovery of >60%. Subsequently, the diluted draw solutions were subject to a nanofiltration (NF) step to regenerate their original osmotic pressure and to simultaneously collect a final permeate product. Magnesium chloride and sodium sulfate were both suitable draw solutes for this application. MgCl2 had a larger specific reverse salt flux and induced a more pronounced fouling-related flux decline with groundwater samples. Na2SO4 was re-concentrated with a higher permeability NF membrane but may require the use of anti-scalants. The average fluxes obtained in high-recovery batch FO were between 5 and 11 L m−2h−1 with an initial bulk draw osmotic pressure in the range of 12–15 bar. Relatively low flux decline was observed in fouling experiments with both samples, while physical cleaning proved promising to recover the related loss in productivity. The final product waters were all of very high quality, suggesting the potential of this coupled system for water reuse and desalination. Some challenges related to the relatively low water flux in the FO step, as well as the loss of draw solutes and the gradual change in composition of the draw solution, need further analysis to establish the technical and economic feasibility of the system. [Display omitted] •Forward osmosis coupled with nanofiltration confirms potential for upscaling.•The system allows wastewater reuse and desalination of brackish groundwater.•Relatively low water flux in forward osmosis is one of the limiting factors.•Loss of draw solute and composition change should be addressed for reconcentration.•Preliminary fouling experiments suggest low irreversible flux decline.